Effective Teaching Methods in a diverse and challenging higher education class in the UK - Usmani, Muhammad Faisal; Alharahsheh, Husam (Advances in Social Sciences Research Journal, 2020)
Education in a multi-cultural environment also requires the participants (international students whose first language is not English) and local students (whose first language is English) to adapt themselves to the environment of education. There should be a two-way process of integration of students into the higher education sector in the UK or elsewhere in order to make the learning process effective. In this process, the teachers/lecturers should determine and adopt the method(s) which would be most appropriate to make teaching interesting and understandable for local and overseas students with a variety of cultural backgrounds. On the other hand, foreign methods of teaching should be regarded by overseas students as part of their learning process so that they are able to accept the best aspects of foreign methods of teaching. It is to be emphasised however that teachers in the higher education system in the UK or elsewhere should, during the initial stage of teaching on any programme, familiarise overseas students with the special aspects of teaching under this system, and alert students, in a friendly manner, of the essentials and techniques of learning and the evaluation system(s) thereto. Teachers/lecturers should be aware of an almost total transformation of a learning method which many of the overseas students are required to go through and also local students feel to be convenient in accordance to the British education system (Helmi and Pius, 2018a; Helmi et al., 2018a; Helmi et al., 2018b and Helmi et al., 2018c). Students must have satisfied the admission requirements of the institutions concerned for a particular programme of study; thus their ability to understand the basic concepts relating to a variety of subjects which they opt for may not be questioned (Helmi and Pius, 2018a).